New insights into the biotechnology and therapeutic potential of Lippia alba (Mill.) N.E.Br. ex P. Wilson. Issue 6 (2nd November 2021) - Malik, Sonia; Odeyemi, Samuel; Pereira, Glaucia C.; Freitas, Luciano Mamede de; Abdul-Hamid, Hazandy; Atabaki, Narges; Makhzoum, Abdullah; Almeida, Eduardo Bezerra de; Dewar, John; Abiri, Rambod
ABSTRACT: Lippia alba, commonly known as Bushy Matgrassis a well-known traditional herb. Besides being used as a food supplement, for seasoning and as a drink, this plant species possess several pharmacological properties, allowing its use in folk medicines to treat various diseases, especially those related to digestive and respiratory conditions. These properties are mainly attributed to the presence of compounds such as myrcene, linalool, β-ocimene, α-guaiene, germacrene, carvone, limonene, eucalyptol, camphor, caryophyllene, neral, geranial and piperitone in the essential oils of  L. alba . Variation in essential oil components and the high phenotypical plasticity of  L. alba  provide a strong evidence of an exciting high number of chemotypes in this aromatic herb. In the current review, we report the botanical, geographical and ecological features of  L. alba . In addition, chemical composition of essential oil is addressed followed by  in vitro  and high efficiency micropropagation protocols. Finally, the therapeutic potential of  L. alba  against important non-communicable diseases is discussed.